Measles, month of birth, and Crohn's disease. Issue 6 (1st December 2000) - Haslam, N; Mayberry, J F; Hawthorne, A B; Newcombe, R G; Holmes, G K T; Probert, C S J
Abstract : BACKGROUND: The rise in the incidence of Crohn's disease (CD) suggests the role of an environmental factor in the development of the disease in susceptible individuals. Perinatal exposure to infection has been proposed as such an environmental factor. AIM: To investigate the influence of birth date on the development of CD in later life. PATIENTS AND METHOD: Four registers of patients with CD, diagnosed from 1972 to 1989, were combined, and data from 1624 patients were examined. The birth dates of CD patients were compared with national birth figures for three decades (1941–50, 1951–60, and 1961–70) to avoid temporal changes in birth trends, and year of birth was compared with epidemic measles years between 1951 and 1967. Risk ratios with 95% confidence intervals (CI) and χ 2 tests were performed. RESULTS: There were marginal differences between the birth dates of the CD patients and those predicted from the general population. Further analysis of both season of birth and year halves revealed a very weak association with the first half of the year (relative risk 1.14 (95% CI 1.01–1.30)). There was no association between developing CD and birth during measles epidemics between 1951 and 1967. CONCLUSIONS: In utero or perinatal exposure to seasonal environmental factors are unlikely potential aetiological agents in the later development of CD.